Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): Venezuelan equine encephalitis - More, Simon (EFSA J, 2017)
Venezuelan equine encephalitis (VEE) has been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on the eligibility of VEE to be listed, Article 9 for the categorisation of VEE according to disease prevention and control rules as in Annex IV and Article 8 on the list of animal species related to VEE. The assessment has been performed following a methodology composed of information collection and compilation, expert judgement on each criterion at individual and, if no consensus was reached before, also at collective level. The output is composed of the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. Details on the methodology used for this assessment are explained in a separate opinion. According to the assessment performed, it is inconclusive whether VEE is eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL because there was no full consensus on the criterion 5 A(v). Consequently, since it is inconclusive whether VEE can be considered eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL, the assessment on compliance of VEE with the criteria as in Sections 4 and 5 of Annex IV to the AHL, for the application of the disease prevention and control rules referred to in points (d) and (e) of Article 9(1), and which animal species can be considered to be listed for VEE according to Article 8(3) of the AHL is also inconclusive.